1998
DOI: 10.1046/j.1537-2995.1998.381098440858.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of immediate adverse effects associated with apheresis donation

Abstract: Apheresis donation is a safe undertaking, suitable for voluntary blood donors, with a very low risk of serious adverse effects. The risk of unconsciousness is lower than that found in many studies of whole-blood donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
87
6
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 12 publications
15
87
6
4
Order By: Relevance
“…Adverse effects of leukapheresis were evaluated retrospectively until December 1999 and prospectively recorded from January 2000 according to the Hemapheresis Committee of the American Association of Blood Banks questionnaire. 7 Each different course of chemotherapy the patient received before the apheresis was counted as a chemotherapy cycle in Table 1. CD34 + cell determination was performed as previously reported. 6 Two million CD34 + cells/kg body weight (BW) was established as the minimum CD34 + cell dose required, and 5 ϫ 10 6 CD34 + cells/kg BW was considered to be an optimum collection.…”
Section: Methodsmentioning
confidence: 99%
“…Adverse effects of leukapheresis were evaluated retrospectively until December 1999 and prospectively recorded from January 2000 according to the Hemapheresis Committee of the American Association of Blood Banks questionnaire. 7 Each different course of chemotherapy the patient received before the apheresis was counted as a chemotherapy cycle in Table 1. CD34 + cell determination was performed as previously reported. 6 Two million CD34 + cells/kg body weight (BW) was established as the minimum CD34 + cell dose required, and 5 ϫ 10 6 CD34 + cells/kg BW was considered to be an optimum collection.…”
Section: Methodsmentioning
confidence: 99%
“…Many authors have reported the apheresis as a safer procedure which is associated with less frequent adverse donor reactions as compared to whole blood donations [2,3]. A multi-centric study reported the frequency of adverse reactions observed in apheresis donations ranges from 0.32 to 6.81 % [4]. Though these apheresis procedures share a few common adverse events with the whole blood donations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…), these are associated with few unique adverse events which are not associated with standard phlebotomies and/or whole blood donations [2,3]. These may be attributed to the usage of anticoagulant 'Acid-Citrate-Dextrose' (ACD) causing hypocalcemia and longer donation periods [4].…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that unstimulated leukapheresis product collections are low risk donations. McLeod et al, 7 surveyed centres that had performed nearly 20 000 apheresis procedures. The overall incidence of adverse events was 2.2% with more than half (1.2%) being pain or haematoma at the venipuncture site.…”
Section: Introductionmentioning
confidence: 99%